ANALISIS DAN SIMULASI SISTEM HIBRIDA AUTOMATIC VOLTAGE REGULATOR MENGGUNAKAN LINEAR IMPULSIVE SYSTEMS - MARTIN TANURAHARDJA, DONN
Automatic Voltage Regulator (AVR) systems are a class of hybrid systems where their dynamic has impulsive phenomenon. Because of this impulsive phenomenon, it is of interest to study the dynamic behavior using Linear Impulsive Systems (LIS). The hybrid system model of AVR, studied in this thesis, is an AVR system with tap-changing transformer between 1, 0375 Â– 1,1, which has the best result if the voltage supply deadband is between 208 Â— 233,825 volt. This AVR system is controlled by an impulsive controller. The behavior of the hybrid system of AVR with an impulsive controller is simulated using SimulinkTM and StateflowTM. Analysis and simulation of this hybrid system model of AVR model are based on a simple AVR model. Impulsive phenomenon in the AVR model results in a complex and interesting dynamic behavior. The analysis of the AVR system using LIS shows that the AVR system is controllable, is not an asymptotically stable equilibrium and has periodic solution within limit e = 13,794 and the controller has unlimited liveness.